Class or location? What explains the rising tide of absolute global income inequality during 1850-2010? (2015)
This paper is the first to decompose absolute global income inequality into its within-country class and between-country location components. The estimates show that until 1970 locational income differences were the main driver of absolute global inequality, whereas its recent growth can be explained primarily by class differences. Nowadays, inequality between classes explains 70% of absolute global market inequality. Additional findings are that absolute income convergence between countries took place after 2005, that it is possible to reduce absolute inequality and to grow at the same time, and that of late within countries net inequality was growing faster than market inequality.